Isolation synthesis and glycosidase inhibition profile of 3-epi-casuarine - Van Ameijde, J; Horne, G; Wormald, M; Dwek, R; Nash, R; Jones, P; Evinson, E; Fleet, G (2006)
3-epi-Casuarine, the first naturally occurring stereoisomer of casuarine, was isolated from Myrtus communis L. The glycosidase inhibition profile and NMR spectra of 3-epi-casuarine are compared with those of casuarine; the change in configuration at one of the six stereogenic centres causes a dramatic change in the conformation of the bicyclic system. The key step in the 6% overall yield synthesis of 3-epi-casuarine from d-gluconolactone is the efficient cyclization of a completely unprotected pentahydroxyaminomesylate to the pyrrolizidine nucleus. A low yield synthesis of casuarine is also reported. © 2006 Elsevier Ltd. All rights reserved.